Leveraging Researcher Reflexivity to Consider a Classroom Event over Time: Reflexive Discourse Analysis of 'What Counts'. Issue 1 (2nd January 2017) - Anderson, Kate T.
Abstract: This article presents a reflexive and critical discourse analysis of classroom events that grew out of a cross-cultural partnership with a secondary school teacher in Singapore. I aim to illuminate how differences between researcher and teacher assumptions about what participation in classroom activities should look like came into high relief when put into practice. To better understand these differences, I consider the sources and outcomes of what I initially experienced as a visceral tension while observing a series of classroom events as part of a unit that our research team co-designed with a partner teacher. I consider my researcher assumptions, both initial and retrospective, and their role in shaping and sometimes clouding my analytic lens. This article considers multiple vantage points on what comes to be valued, and how, in educational research contexts. By tracing analyses across stages of research, I illustrate how observable moments in time are not phenomena unto themselves but rather are part of the ongoing, developing interpretive process. Implications speak to the importance of reflexively engaging close discourse analyses of classroom events and researchers' roles in shaping them, during and after the fact, through transparency about the recontextualization that analysis entails.